Pengaruh Suction Terhadap Kadar Saturasi Oksigen Pada Pasien Koma Di Ruang ICU RSUD Dr. Moewardi Surakarta Tahun 2015 - Afif Muhamad Nizar; Dwi Susi Haryati ((JKG) Jurnal Keperawatan Global, 2017)
Abstract : Saturation Of Oxygen, Suction, Coma Patients. Decreas consciousness and coma is very deep response. Comatose patients often experience problems mainly due to accumulation of secretions that coma patients decreased cough reflex. So that the patient needs to be done to free the airway suctioning of secretions. A phenomenon that occurs in the ICU Hospital Dr. Moewardi almost comatose patients conducted periodically suction approximately every 2 hours.The purpose of this study was to determine the effect of suction on oxygen saturation in patients with coma in the ICU Hospital Dr. Moewardi Surakarta 2015. This type of research is quasy experimental research design is a one-group pretest-posttest design and analysis using paired samples T-test.Based on the results of the Shapiro-Wilk normality test can be concluded that the data tedistribusi normal. So using a paired samples T test with significance value (p) was 0.000, which is the value of p <0.05. This means that there is an average difference of oxygen saturation value before the suction action after the suction action. Oxygen saturation difference is -1.79, meaning that oxygen saturation values prior to suction smaller than the value of the oxygen saturation after the suction.